Transdermal nicotine patch enhances type I collagen synthesis in abstinent smokers - Sørensen, Lars T.; Jorgensen, Lars N.; Zillmer, Rikke; Vange, Jakob; Hemmingsen, Ulla; Gottrup, Finn (Wound repair and regeneration, 2006)
ABSTRACT Cigarette smokers deposit less collagen, expressed as hydroxyproline, in granulation tissue than nonsmokers. We studied the effect of abstinence from smoking and transdermal nicotine patches on deposition of hydroxyproline, proline, type I procollagen, and total proteins. Fifty‐four healthy smokers were studied during 10 days of smoking and again from days 10 to 20 following smoking cessation. After the first 10 days of abstinence they were randomized to double‐blind treatment with transdermal nicotine patches of 25 mg/day or placebo for a period of 10 days. During this period and during smoking, an expanded polytetrafluoroethylene tube was implanted into the subcutis. Following removal of the implant, total amino acids and peptides were extracted. Hydroxyproline and proline were analyzed by high‐pressure liguid chromatography, type I procollagen was analyzed by enzyme‐linked immunoassay, and total proteins were determined colorimetrically. In the 39 subjects who complied with the study protocol, abstinence from smoking did not affect the deposition of hydroxyproline, proline, type I procollagen, or total protein in the implants. During abstinence, the type I procollagen level increased by 18% in the transdermal nicotine patches group and decreased by 10% in the placebo group (p<0.05). We conclude that 20 days of abstinence from smoking does not affect collagen deposition in granulation tissue. However, in abstinent smokers, transdermal nicotine patches appears to increase type I collagen synthesis.